Analisis Hukum Zakat Hasil Perkebunan Kelapa Sawit berdasarkan Prinsip Zakat Pertanian - Zubaidah Assyifa; Rifqil Khairi; Muhammad Zakir; Wahyu Febri Ramadhan Sudirman; Rinda Fitriyana (EL-EMIR Institute, 2026)
This study aims to analyze the zakat law on oil palm plantation yields based on the principles of agricultural zakat from an Islamic legal perspective. The study employed a qualitative approach with library research. Data were obtained from the Quran, hadith, fiqh books, scientific journals, and various literature related to agricultural zakat and oil palm plantation zakat. Data collection was conducted through documentation studies, while data analysis employed a descriptive-analytical method with a normative sharia approach. The results show that oil palm has productive characteristics and economic value, thus fulfilling the basic principles of zakat obligations. Scholars differ in their opinions regarding the status of zakat on oil palm, with some classical scholars limiting agricultural zakat to certain food crops, while contemporary scholars extend the obligation to all productive plantation products. This study also found that low public understanding and suboptimal zakat management are the main obstacles to the implementation of zakat on oil palm. Therefore, education and strengthening of zakat institutions are needed so that the potential of zakat on oil palm can be utilized to improve community welfare and economic equality.